A randomized controlled intervention to promote readiness to genetic counseling for breast cancer survivors. Issue 5 (11th April 2019) - Kasting, Monica L.; Conley, Claire C.; Hoogland, Aasha I.; Scherr, Courtney L.; Kim, Jongphil; Thapa, Ram; Reblin, Maija; Meade, Cathy D.; Lee, M. Catherine; Pal, Tuya; Quinn, Gwendolyn P.; Vadaparampil, Susan T.
Abstract: Objective: Breast cancer (BC) survivors with a genetic mutation are at higher risk for subsequent cancer; knowing genetic risk status could help survivors make decisions about follow‐up screening. Uptake of genetic counseling and testing (GC/GT) to determine BRCA status is low among high risk BC survivors. This study assessed feasibility, acceptability, and preliminary efficacy of a newly developed psychoeducational intervention (PEI) for GC/GT. Methods: High risk BC survivors (N = 119) completed a baseline questionnaire and were randomized to the intervention (PEI video/booklet) or control (factsheet) group. Follow‐up questionnaires were completed 2 weeks after baseline (T2), and 4 months after T2 (T3). We analyzed recruitment, retention (feasibility), whether the participant viewed study materials (acceptability), intent to get GC/GT (efficacy), and psychosocial outcomes (eg, perceived risk, Impact of Events Scale [IES]). t tests or chi‐square tests identified differences between intervention groups at baseline. Mixed models examined main effects of group, time, and group‐by‐time interactions. Results: Groups were similar on demographic characteristics ( P ≥ .05). Of participants who completed the baseline questionnaire, 91% followed through to study completion and 92% viewed study materials. A higher percentage of participants in the intervention group moved toward GC/GT (28% vs 8%; P = .027). Mixed models demonstrated significant group‐by‐time interactions for perceived risk ( P = .029), IES ( P = .027), and IES avoidance subscale ( P = .012). Conclusions: The PEI was feasible, acceptable, and efficacious. Women in the intervention group reported greater intentions to pursue GC, greater perceived risk, and decreased avoidance. Future studies should seek to first identify system‐level barriers and facilitators before aiming to address individual‐level barriers.